2002
DOI: 10.1002/1521-3757(20021104)114:21<4294::aid-ange4294>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Der bislang aktivste Katalysator für die Suzuki‐Kupplung von aktivierten Arylchloriden wird durch Zugabe von Tricyclohexylphosphan zum katalytisch inaktiven Komplex 1 erhalten. Mit 1 gelingt die Kupplung sogar mit elektronisch desaktivierten Kupplungspartnern [Gl. (1); z. B. Ar=C6H4‐4‐OMe, Ar′=Ph].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Nevertheless, it is frequently speculated that the second ligand may behave as a co-ligand to provide a catalyst reserve rather than forming a new catalytic species, thereby increasing the longevity of the catalyst. [15] Also, Percec hypothesized that both ligand and co-ligand played an important role in the conversion of Ni II precatalyst to Ni 0 active catalyst as well as in the catalytic cycle. Clearly, this proposed mechanism involving mixed-bidentate-ligand systems is quite different from that proposed by Reetz for mixed-monodentate-ligand systems (Scheme 2A).…”
Section: Mixed-bidentate-ligand Systemsmentioning
confidence: 99%
“…Nevertheless, it is frequently speculated that the second ligand may behave as a co-ligand to provide a catalyst reserve rather than forming a new catalytic species, thereby increasing the longevity of the catalyst. [15] Also, Percec hypothesized that both ligand and co-ligand played an important role in the conversion of Ni II precatalyst to Ni 0 active catalyst as well as in the catalytic cycle. Clearly, this proposed mechanism involving mixed-bidentate-ligand systems is quite different from that proposed by Reetz for mixed-monodentate-ligand systems (Scheme 2A).…”
Section: Mixed-bidentate-ligand Systemsmentioning
confidence: 99%
“…Most catalytic reactions with triarylphosphite palladacycles have been performed in organic solvents; however, successful application of ionic liquids as reaction media has also been reported [6]. Interestingly, an increase in the catalytic activity of dimeric palladacycles has been observed after their transformation to monomeric complexes in reaction with mono-or bi-dentate phosphorus ligands [4,9]. Particularly high activity in the crosscoupling of deactivated aryl chlorides has been noted for palladium derivatives containing PCy 3 [9].…”
Section: Introductionmentioning
confidence: 99%
“…5 We have recently found that the PCy 3containing complexes 1 and 2, the latter of which is typically formed in situ from 3 and PCy 3 , show good and excellent activity respectively in the Suzuki coupling of aryl chlorides. 6 We now find that not only the PCy 3 complexes shown, but also simple systems formed in situ from palladium acetate give, to the best of our knowledge, the highest activity yet reported in the Stille coupling of deactivated and non-activated aryl chlorides.…”
mentioning
confidence: 68%